2009
DOI: 10.1016/s1607-551x(09)70052-x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid Angiomyolipoma of the Kidney Mimicking Renal Cell Carcinoma: A Clinicopathologic Analysis of Cases and Literature Review

Abstract: Classical renal angiomyolipoma (AML) is a common tumor that, in most cases, follows a benign course and has clearly defined radiologic and histological characteristics. However, rare cases of clinically aggressive or malignant AML, the epithelioid variant of AML (EAML), have been reported. Here, we review the five cases of EAML diagnosed since 2000 at our institution to highlight the spectrum of clinical, radiological and histological characteristics. In all cases, renal lesions seen on computed tomography (CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 15 publications
3
46
1
Order By: Relevance
“…Both cases of epithelioid AML in this study contained no fat in CT and MRI and therefore, RCC was suspected. This finding confirms and extends those previously reported by Varma et al [8], Tsai et al [35], and Lane et al [42]. On the contrary, it is contradicted with that of Chen et al [43] who reported a case of aggressive epithelioid AML which showed fat by both CT and MRI.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Both cases of epithelioid AML in this study contained no fat in CT and MRI and therefore, RCC was suspected. This finding confirms and extends those previously reported by Varma et al [8], Tsai et al [35], and Lane et al [42]. On the contrary, it is contradicted with that of Chen et al [43] who reported a case of aggressive epithelioid AML which showed fat by both CT and MRI.…”
Section: Discussionsupporting
confidence: 88%
“…Both cases were negative for S-100 and cytokeratin. Similar findings were documented by Varma et al [8], Tsai et al [35], and Aydin et al [47]. On the contrary; Yang et al [1] reported strong SMA and actin in epithelioid AML and moderate HMB-45 staining.…”
Section: Discussionsupporting
confidence: 85%
“…Although a large majority of AMLs with focal epithelioid components are benign, pure epithelioid renal AML (EAML), a rare subgroup characterized by the presence of epithelial cells staining strongly for melanomaassociated markers, may become locally invasive and spread by affecting renal veins and inferior vena cava (16). Those aggressive epithelioid "carcinoma-like" variants are highly cellular with very little or no fat, tend to be larger and may become symptomatic for the majority (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, all small hypo-echoic AMLs showed homogeneous enhancement, significantly higher than that in size-matched ccRCCs [17]. Furthermore, it is also a feature on contrast-enhanced computed tomography (CECT) [18]. This is probably a result of the uniform solid component in AMLs, which do not display any hemorrhage, cystic change, or necrosis.…”
Section: Discussionmentioning
confidence: 81%